Does duration of the marriage affect the marital adjustment of postgraduate Iranian students in Malaysia? - Ghoroghi, Soudabeh; Hassan, Siti Aishah; Baba, Maznah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
The aim of this study was to investigate the relationships between duration of marriage and marital adjustment in a sample of married postgraduate Iranian students in Malaysia. As the popularity of studying in Malaysia among Iranian students at postgraduate level .is increasing, more studies are needed among this population. An online self-administered questionnaire conducted to assess the studied variables. Data collected from 220 married students who were selected randomly to participate in the study through their email addresses. The respondents were questioned about their demographic information and completed Locke-Wallace Marital Adjustment Test (LWMAT; Locke & Wallace, 1959). Data analysis provided information about frequencies, percentages, mean scores and Pearson's correlation. The results disclosed that there was no correlation between length of marriage and marital adjustment. It indicates that marital adjustment remained fairly stable over time.